The coronavirus as test of resistance to European integration: limits of constitutional dialogue - Pazos-Vidal, Serafin (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
This article aims to provide an analysis of the European Union’s response to the coronavirus crisis, particularly in relation to multilevel relations with Member States. The mainly financial response to the crisis and the political and legal readings of it are examined. The Coronavirus is conceived as an accelerator of the integration process. The possible need for expansion of competencies and the performance of institutions are considered. The Next Generation EU recovery plan is examined and specifically the post-COVID-19 structural reforms. Finally, the validity of multilevel constitutionalism in the times of coronavirus is examined under the Weiss judgment of the German constitutional court.